Spatial autocorrelation of stunting prevalence among children under five years in West Bandung Regency in 2022 - Minawati; Trihandini, Indang; Sipahutar, Tiopan; Salsabila, Syefira (Universitas Gadjah Mada, 2024)
Purpose: This study aims to determine whether there is spatial autocorrelation based on the prevalence of stunting and their spatial diffusion pattern. It also aims to find areas that will become stunting hotspots and cold spots area in West Bandung Regency in 2022. Method: This research employed an ecological study design using spatial analysis to estimate and analyze the distribution pattern of stunting prevalence in the West Bandung Regency in 2022. The data used results from a child monitoring record in Posyandu (Integrated Service Post) carried out by the West Bandung Regency Health Office regarding the prevalence of stunting among children under five years. This study used Moran Index and Local Indicators Autocorrelation (LISA) for spatial pattern analysis. Results: This study shows that there is negative spatial autocorrelation, or the distribution of stunting prevalence forms a random pattern (I<E). This study also indicates that there is statistically no spatial correlation between sub-district areas based on stunting prevalence in West Bandung Regency in 2022 (p-value > 0,05). There is no hotspot and cold spot area of stunting in West Bandung Regency in 2022. Conclusion: The prevalence of stunting in West Bandung Regency in 2022 is not spatially related between sub-district areas, with a random or scattered pattern. The area that is the main priority for intervention is Saguling Subdistrict, the subdistrict with the highest prevalence of stunting. The intervention program implemented in Cililin Subdistrict can be implemented in Saguling Subdistrict to reduce stunting prevalence.